TST36 stapling for rectocele and hemorrhoidal prolapse – early results of the prospective German multicenter study - Petersen, Sven; Sterzing, Daniel; Ommer, Andreas; Mladenov, Assen; Nakic, Zrino; Pakravan, Faramaz; Wolff, Katja; Lorenz, Eric P. M.; Prosst, Ruediger L.; Sailer, Marco; Scherer, Roland (GMS German Medical Science, 2016)
Introduction: The aim of the study was to evaluate the safety and feasibility of stapled transanal procedures performed by a 36 mm stapling device, the so-called TST36 stapler.Methods: From September 2013 to June 2014 a prospective observational study was carried out by 8 proctology centers in Germany. The Cleveland Clinic Incontinence Score (CCIS) for incontinence and the Altomare ODS score were determined preoperatively. Follow-up examinations were performed after 14 days, one month and 6 months, at this time both scores were reevaluated.Results: 110 consecutive patients (71 women, 39 men) with a mean age of 59.7 years (±13.8 years) were included in the study. The eight participating institutes entered 3 to 31 patients each into the study. The indication for surgery was an advanced hemorrhoidal disease in 55 patients and ODS with rectal intussusception or rectocele in 55 patients. Mechanical problems with stapler introduction occurred in (20%) and a partial stapleline dehiscence in 4 cases (3.6%). Additional stitches for bleeding from stapleline were necessary in (78.2%). Reintervention was necessary for bleeding 7 times (6.3%). Severe complications during follow-up were stapleline dehiscence in one case and recurrent hemorrhoidal prolapse in 5 cases (4.5%). Altomare ODS score and CCIS improved significantly after surgery.Conclusions: Despite a notable complication rate during surgery and the postoperative period, the TST36 can be considered as an effective tool for low rectal stapling for anorectal prolapse causing hemorrhoids or obstructed defecation.